Review of grapefruit juice-drugs interactions mediated by intestinal CYP3A4 inhibition - Wael Abu Dayyih, Israa Al-Ani, Mohammad Hailat, Samia Milhem Alarman, Zainab Zakaraya, Mohammad Abu Assab, Enas Alkhader (Journal of Applied Pharmaceutical Science, 2024)
Grapefruit is a citrus fruit that belongs to the Rutaceae family. One large grapefruit yields around 200–250 ml of juice, consumed regularly by many individuals owing to its nutritional value, including fiber, vitamin C, and antioxidants. Grapefruit juice (GFJ) compounds, mainly naringin, bergamottin, and 6,7-dihydroxybergamottin (DHB), inhibit intestinal CYP3A4 enzymes, which are mediated by the metabolic processes of many drugs and result in the interaction between GFJ and drugs that are CYP3A4 substrates when administered concomitantly. GFJ-drug interaction is affected by several factors, including oral bioavailability, patient vulnerability, and factors related to GFJ consumption, such as the amount of GFJ consumed and the interval between GFJ and drug administration. Many drugs from different classes have the potential for interaction, including calcium channel blockers such as felodipine, statins such as simvastatin, immunosuppressants, benzodiazepines such as midazolam, antihistamines such as terfenadine, and many other drugs. Pharmacists have a strong medical background that makes them able to predict grapefruit-drug interactions. Thus, they play a critical role in reducing the risk of GFJ-drug interactions by advising and educating patients when dispensing prescribed and Over-the-counter (OTC) drugs.
Keywords: Grapefruit, cytochrome P3A4, CYP3A4, drug-food interaction, furanocoumarin